2014
DOI: 10.1057/ajp.2014.5
|View full text |Cite
|
Sign up to set email alerts
|

Silence as the Voice of Trauma

Abstract: Silence is a key to the unspoken world of the patient. Rather than interpreting silence as a defensive maneuver, the analyst may understand this disruption as a royal road to the patient's traumatic experiences. The author proposes to recognize traumatic silences in the analytic process and the transference as a re-experiencing of past, unpredictable traumatic affective states and memories. Silences in this context are both a repeat of a disconnecting experience as well as a manifestation of a silencing identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…In psychotherapy, silence can be used deliberately or autonomically by patients to defend against perceived traumatic intrusions which may also be useful therapeutically as a path toward understand the traumatic past (Dimitrijevic, 2021b; Ritter, 2014). Since silence also can indicate a lack of words for early traumatic experiences, the space of noncommunication can enable restoring and articulation of previously disorganizing and incomprehensible experiences.…”
Section: Self-silencing and Traumamentioning
confidence: 99%
“…In psychotherapy, silence can be used deliberately or autonomically by patients to defend against perceived traumatic intrusions which may also be useful therapeutically as a path toward understand the traumatic past (Dimitrijevic, 2021b; Ritter, 2014). Since silence also can indicate a lack of words for early traumatic experiences, the space of noncommunication can enable restoring and articulation of previously disorganizing and incomprehensible experiences.…”
Section: Self-silencing and Traumamentioning
confidence: 99%
“…Silence is often regarded as an expression of deep trauma. Maria Ritter (2014) in her article "Silence as the Voice of Trauma" says, "Silence is a key to the unspoken world of the patient. Rather than interpreting silence as a defensive maneuver, the analyst may understand this disruption as a royal road to the patient's traumatic experiences."…”
Section: Parallel Presentation Of Ayesha and Behulamentioning
confidence: 99%
“…In her investigation of the phenomenon in Holocaust survivors, Ritter (2014) found that projective identification was a core mechanism by which trauma was transmitted to offspring. Parents who projected Holocaust-related feelings and anxieties into children often had children who introjected them and who would, as a result, behave as though they had directly experienced concentration camps and other Nazi atrocities, themselves.…”
Section: Intergenerational Racial Traumamentioning
confidence: 99%
“…It is the wilful or unconscious desire to avoid distressing material. Denial is a common psychological defence against trauma (APA, 2018; Ritter, 2014). And, like many responses to trauma, as previously discussed, it is not limited to individual survivors, their family members or direct witnesses.…”
Section: Silence Power and The Social Unconsciousmentioning
confidence: 99%